Global leadership perspectives : insights and analysis - Simon Western; Éric-Jean Garcia (London : SAGE Publications, 2018)
In 'Global Leadership Perspectives, ' the editors have collated insights into leadership from a diverse set of authors in 20 countries and regions around the world, including socio-cultural analysis from experts in China, Brazil and Ethiopia. The book is split into two parts; its first part presents the local and regional variations in leadership from across the globe, with each of the 20 individual authors presenting the histories, cultures, tensions and social changes that shape the practice of everyday leadership in their respective region. In the second part, the editors then critically analyses these chapters and identify the key themes and specific issues, enabling the reader to challenge their own leadership perceptions and move beyond the normative, uncritical approach to leadership
Keywords: Cross-cultural studies; Leadership Cross-cultural studies